Academic Senate Minutes 2011-04-14 - Academic Senate:::::::::
Chair Report. Agenda approved. Minutes of 3/24/11 approved. Nursing BSN revision – approved. Kinesiology Physical Education revision – approved. Intellectual Property Policy – First reading completed. Revision to the Course Repeat Policy amended and approved. Report: Waitlist on CMS. Revision to Class Attendance Policy – Second Reading, motion on the floor. FSAC Report. President Report. Provost Report. Good of the Order: Remembering Bob Coleman-Senghor.